2022
DOI: 10.1002/bse.2940
|View full text |Cite
|
Sign up to set email alerts
|

Industry 4.0 technologies and circular economy: The mediating role of supply chain integration

Abstract: There is a great expectation that Industry 4.0 technologies will enable better circular economy (CE) results at firms. However, it is unclear how these technologies might contribute to CE. We hypothesize that Industry 4.0 technologies are positively related to the level of integration among actors along the supply chain and within the firm supply chain integration (SCI), which, in turn, explains superior CE results. By employing partial least square structural equation models on original survey data based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 110 publications
(172 reference statements)
3
55
0
Order By: Relevance
“…Our study has revealed that there was a sudden surge in the number of publications in the above-mentioned influential journals, especially in the Journal of Cleaner Productions and Sustainability (Switzerland), after 2015. This substantiates the increased attention given to this field of research to integrate technological development in achieving sustainability by creating an SSC related to various industries and sectors (DiMaria et al, 2022;Khan, Razzaq, et al, 2021).…”
supporting
confidence: 66%
“…Our study has revealed that there was a sudden surge in the number of publications in the above-mentioned influential journals, especially in the Journal of Cleaner Productions and Sustainability (Switzerland), after 2015. This substantiates the increased attention given to this field of research to integrate technological development in achieving sustainability by creating an SSC related to various industries and sectors (DiMaria et al, 2022;Khan, Razzaq, et al, 2021).…”
supporting
confidence: 66%
“…The gap SMEs face when compared to large firms in getting economic rewards from their sustainable production practices suggests there is room for policies for sustaining the introduction of CE to help them overcoming innovation barriers (as discussed in Ghisetti et al, 2017) which may be specific to the typology of innovation considered, as discussed in García‐Quevedo et al (2020), who also stress that most CE disruptive innovators who redesign goods to reduce materials experience all of the possible existing barriers. Those policies may either be directly aimed at supporting innovation via for instance public funding (Cecere et al, 2020) or public procurement (Ghisetti, 2017) or indirectly aimed at stimulating certain features that facilitate the adoption of CE technologies, such as their internationalization (Chiarvesio et al, 2015), collaboration practices and networking activities with other firms to acquire knowledge from different sources (De Marchi, 2012) or supply‐chain integration (di Maria et al, 2022). Such policies, either direct or indirect, are especially needed for SMEs, who are shown in this study to face potential short‐term negative impacts through the adoption of CE practices.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a case study of the electricity firm Piclo Flex, the article shows that digital platforms can integrate multiple design themes within hybrid business models to tackle tensions between for‐profit and for‐purpose objectives. However, as Di Maria et al (2021) survey results reveal, even when the intentions are there, full sustainable benefits will only be realized under certain conditions (Point 2). Their study provides evidence that adopting Industry 4.0 technologies in supply chains (i.e., smart manufacturing technologies and data processing technologies) can have positive circular economy results but requires stakeholder collaboration to realize the full sustainable outcome.…”
Section: Intended and Unintended Consequences Of Digitalization For S...mentioning
confidence: 99%
“…Based on a case study of the electricity firm Piclo Flex, the article shows that digital platforms can integrate multiple design themes within hybrid business models to tackle tensions between forprofit and for-purpose objectives. However, as Di Maria et al (2021) survey results reveal, even when the intentions are there, full sustainable benefits will only be realized under certain conditions (Point 2).…”
Section: Properties Of Digital Technologies and Their Unintended Cons...mentioning
confidence: 99%